Harvesting microwave energy using pyroelectricity of nanostructured graphene/zirconium-doped hafnium oxide ferroelectric heterostructures. (6th March 2023) - Dragoman, Mircea; Aldrigo, Martino; Dinescu, Adrian; Vasilache, Dan; Iordanescu, Sergiu; Dragoman, Daniela; Laudadio, Emiliano; Pavoni, Eleonora
Abstract: In this work, we present the design, atomistic/circuit/electromagnetic simulations, and the experimental results for graphene monolayer/zirconium-doped hafnium oxide (HfZrO) ultra-thin ferroelectric-based field effect transistors fabricated at the wafer scale, regarding the pyroelectricity generation directly from microwave signals, at room temperature and below it, namely at 218 K and at 100 K. The transistors work like energy harvesters, i.e. they collect low-power microwave energy and transform it into DC voltages with a maximum amplitude between 20 and 30 mV. The same devices function as microwave detectors in the band 1–10.4 GHz and at very low input power levels not exceeding 80 μ W when they are biased by using a drain voltage, with average responsivity values in the range 200–400 mV mW −1 .